2020
DOI: 10.1007/s12262-020-02642-9
|View full text |Cite
|
Sign up to set email alerts
|

Elective Gastrointestinal Surgery in COVID Times

Abstract: With the COVID pandemic claiming deaths the world over, the healthcare systems were overburdened. This led to the cancellation and delay in elective surgical cases which can have far-reaching consequences This study reports our experience of elective gastro-intestinal surgical procedures during the COVID pandemic, after instating preventive strategies and screening protocols to prevent the transmission of COVID infection. This is a case series analysis of elective gastro-intestinal surgical procedures performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
(10 reference statements)
0
18
0
2
Order By: Relevance
“…Significantly fewer surgeries were being performed during the pandemic, with a higher proportion of cancer surgeries than the previous year (44.9% vs. 23.5%, p < 0.001). However, no significant difference in the incidence of major complications and 30-day mortality were observed in the two time periods [14].…”
Section: Elective Surgery For Gastrointestinal Cancermentioning
confidence: 79%
See 2 more Smart Citations
“…Significantly fewer surgeries were being performed during the pandemic, with a higher proportion of cancer surgeries than the previous year (44.9% vs. 23.5%, p < 0.001). However, no significant difference in the incidence of major complications and 30-day mortality were observed in the two time periods [14].…”
Section: Elective Surgery For Gastrointestinal Cancermentioning
confidence: 79%
“…The surgeries for bowel obstruction and ventral hernia increased, while that for acute cholecystitis decreased during the pandemic period. An Indian study by Kapoor et al reported that only 314 gastrointestinal surgeries were performed from March to July 2020 compared to 914 surgeries during the same time in the previous year [14].…”
Section: Impact Of Covid-19 Pandemic On Gastrointestinal Surgical Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies were reviewed for elective surgery outcomes during the COVID-19 pandemic ( Table 2 ) [ 16 17 19 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ]. All of these reports presented postoperative morbidity and mortality data that were comparable to the pre-pandemic era.…”
Section: Resultsmentioning
confidence: 99%
“…There are other studies which use only the heat and moisture exchanger (HME/HMEF) filter in the circuit. [24][25][26] This has been filtering HBV (42 nm) and HCV (30 to 60 nm) with an efficacy of 99.9%. SARS-CoV-2 has a larger diameter of 70 to 90 nm, so we expect a similar or better filtration efficacy.…”
Section: Discussionmentioning
confidence: 99%